Gene Expression Control by Glucocorticoid Receptors during Innate Immune Responses - Xavier, Andre Machado; Anunciato, Aparecida Kataryna Olimpio; Rosenstock, Tatiana Rosado; Glezer, Isaias (Frontiers in Endocrinology, 2016)
Glucocorticoids (GCs) are potent anti-inflammatory compounds that have been extensively used in clinical practice for several decades. GCs effects on inflammation are generally mediated through GC receptors (GRs). Signal transduction through these nuclear receptors leads to dramatic changes in gene expression programs in different cell types, typically due to GR binding to DNA or to transcription modulators. During the last decade the view of GCs as exclusive anti-inflammatory molecules has been challenged. GR negative interference in pro-inflammatory gene expression was a landmark in terms of molecular mechanisms that suppress immune activity. In fact, GR can induce varied inhibitory molecules, including a negative regulator of Toll-like receptors (TLRs) pathway, or subject key transcription factors, such as NF-B and AP-1, to a repressor mechanism. In contrast, the expression of some acute-phase proteins (APPs) and other players of innate immunity generally requires GR signaling. Consequently, GRs must operate context-dependent inhibitory, permissive or stimulatory effects on host defense signaling triggered by pathogens or tissue damage. This review aims to disclose how contradictory or comparable effects on inflammatory gene expression can depend on pharmacological approach (including selective glucocorticoid receptor modulators; SEGRMs), cell culture, animal treatment or transgenic strategies used as models. Although the current view of GR-signaling integrated many advances in the field, some answers to important questions remain elusive.